Facing Global Inflation: Economic Strategies to Strengthen People's Purchasing Power - Priyatna, Hilda Nanda; Suryadi, Ibnu; Ersanti (MSJ : Majority Science Journal, 2025)
Global inflation is a complex economic challenge, influenced by various factors such as supply chain disruptions, energy price fluctuations, and geopolitical instability. This research aims to analyze the economic strategies that can be used to strengthen people's purchasing power amid the global inflation turmoil. The research method used is a qualitative approach with a literature study method, which allows researchers to understand the inflation phenomenon in depth through theoretical studies and analysis from various perspectives. The data used comes from secondary sources that are credible and relevant to the topic of inflation and economic strategy. The results show that a combination of balanced monetary and fiscal policies is the main approach in dealing with inflation. Controlling interest rates and liquidity through monetary policy can maintain price stability and currency value, while appropriate fiscal policies, such as targeted economic stimulus and state spending efficiency, help maintain people's purchasing power without triggering further inflation spikes. In addition, production sector optimization and distribution efficiency also play an important role in reducing costs and ensuring a stable supply of goods. Increasing industrial productivity, diversifying energy sources, and utilizing technology in the supply chain can help reduce price pressures in the market